1997
DOI: 10.1007/s11665-997-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Powder processing and properties of zircon-reinforced Al-13.5Si-2.5Mg alloy composites

Abstract: Zircon, ZrSiO4, is a thermally stable mineral requiring expensive and energy-intensive process to reduce. Owing to its abundance, high hardness, excellent abrasion/wear resistance, and low coefficient of thermal expansion, a low-cost alternative use of the mineral for medium-strength tribology was investigated. The present study has developed a conventional low-cost, double-compaction powder metallurgy route in the synthesis of AI-13.5Si-2.5Mg alloy reinforced with zircon. The mechanical and physical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 16 publications
2
16
0
2
Order By: Relevance
“…The small amounts of impurities effect on the decomposition temperature of zircon and its kinetics and also the formation of low melting liquid phases resulting in the favored dissociation of solid silica immediately after releasing from zircon structure 30 . The formation of a liquid phase reaction sintering at the boundaries of the reaction grains in aluminum alloy matrix composites at 615°C in vacuum for 20 min was reported, leading to the formation of different aluminum compounds or intermetallic phases 20 . These intermetallic phases have been known to be the responsible of good wear properties, high abrasion resistance and good heat resistance.…”
Section: Densitymentioning
confidence: 98%
See 1 more Smart Citation
“…The small amounts of impurities effect on the decomposition temperature of zircon and its kinetics and also the formation of low melting liquid phases resulting in the favored dissociation of solid silica immediately after releasing from zircon structure 30 . The formation of a liquid phase reaction sintering at the boundaries of the reaction grains in aluminum alloy matrix composites at 615°C in vacuum for 20 min was reported, leading to the formation of different aluminum compounds or intermetallic phases 20 . These intermetallic phases have been known to be the responsible of good wear properties, high abrasion resistance and good heat resistance.…”
Section: Densitymentioning
confidence: 98%
“…Aluminum alloy matrix composites reinforced with zircon and alumina particles were successfully synthesized by stir casting method and results showed that hybrid reinforced composites have better hardness and tensile strength than aluminum 19 . Ejiofor et al 20 reported an improvement of the ultimate tensile strength, yield strength and hardness of aluminum alloy composites by adding 15 vol% zircon particles (size < 200 µm). The results of Abdizadeh et al 16,21 experiments also showed that the mechanical properties of aluminum-zircon composites can be optimized with 5 wt% zircon reinforcement at sintering temperature of 650°C.…”
Section: Introductionmentioning
confidence: 99%
“…Por isso, é muito utilizado como matriz para pigmentos cerâmicos. A formação da fase ZrSiO 4 por meio de métodos químicos ocorre por meio de reação entre a fase tetragonal da zircônia (t-ZrO 2 ) e a fase amorfa da sílica (SiO 2 ) [1][2][3][4][5][6].…”
Section: Introductionunclassified
“…Processos de alto custo e de alta energia são necessários para que seja reduzido [1,2]. Por isso, é muito utilizado como matriz para pigmentos cerâmicos.…”
unclassified
“…Most of them employed solidification (such as vortex, preformed infiltration, and casting) and solid-state (such as powder metallurgy) technologies, in which DRACs are produced by directly incorporating reinforcing particles/fibers/whiskers into matrix alloys. [1][2][3][4][5] DRACs produced by these conventional techniques have been competitive for tribological applications; however, they are still not profitable for structural applications. [6] The small-size reinforcing particles, necessary for the superior mechanical properties, are very expensive.…”
Section: Introductionmentioning
confidence: 99%